2021
DOI: 10.1002/ijgo.13854
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives about smoking cessation during pregnancy and beyond of Aboriginal women in Australia: A qualitative analysis using the COM‐B model

Abstract: Objective Aboriginal and Torres Strait Islander women (hereafter Aboriginal) and their babies experience poor health outcomes for which smoking is a major risk factor. This paper explores Aboriginal women's perspectives on and experiences of smoking cessation, within and outside pregnancy, and their use of smoking cessation services using the COM‐B (Capability, Opportunity, Motivation as determinants of Behaviour) model to understand Aboriginal women's capabilities, opportunities, and motivation for smoking ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This mapping approach was unique to this study, although similar approaches have been reported elsewhere in the literature (e.g. Flannery et al, 2018 ; Gould, 2014 ; Rahman et al, 2021 ).…”
Section: Methodsmentioning
confidence: 78%
“…This mapping approach was unique to this study, although similar approaches have been reported elsewhere in the literature (e.g. Flannery et al, 2018 ; Gould, 2014 ; Rahman et al, 2021 ).…”
Section: Methodsmentioning
confidence: 78%
“…The issue highlights the voices of those usually not heard in research, in clinical care, and in health service design, [1][2][3][4][5][6] and calls out the silence and invisibility commonly imposed on Indigenous women. [7][8][9][10][11] This Special Issue includes calls from Indigenous researchers through Indigenous-led and -conducted research; and calls from Indigenous women, either through telling the stories of their health and healthcare journeys, 1,12,13,14 or through risk factors and health outcomes being made visible in quantitative data, 8,15,16 or through looking at existing literature in new ways. 7,9,10,11…”
mentioning
confidence: 99%
“…This is done in order to empower women in healthcare, 12 to develop and trial culturally safe and community-based approaches, 2,6 to partner with communities, 3,5 to employ Indigenous methods and knowledge, 8,14 to privilege Indigenous voices, 4,9,10,11 to move towards risk assessment and management tailored to Indigenous populations and context, 15,16 and to explore women's experiences in new ways. 1,9,13 Much of the research responds to the silence/invisibility of First Nations and Indigenous women by challenging the norms of women's healthcare provision, such as persistent discrepancies in structural/social determinants of health, healthcare access and health outcomes, systemic racism, and trauma.…”
mentioning
confidence: 99%
See 2 more Smart Citations